Shared intentionality in children with Autism Spectrum Disorder (ASD) - Asimenia Papoulidi; Christina F. Papaeliou; Stavroula Samartzi (Ψυχολογία: το Περιοδικό της Ελληνικής Ψυχολογικής Εταιρείας, 2021)
It is well documented that the ability and motivation to engage with others in collaborative activities with joint goals and shared intentions is the foundation of human uniqueness. However, children with Autism Spectrum Disorder (ASD) show difficulties in sharing their motives, intentions, and emotions with others about topics in the environment and manifest low levels of engagement. The purpose of the present study was to compare the level of intentionality and social engagement in 10 children with ASD and 10 typically developing (TD) children, matched for mental age, during free play interactions with their mothers. Children were video recorded while playing with their mothers in a naturalistic condition with toys provided by the researcher. For the microanalysis of the video recordings the EUDICO Linguistic Annotator was used, which permits the analysis of joint behaviors and captures subtle qualitative differences in social engagement. Results indicated that children with ASD showed deficits in joint attention, exhibited no functional play and employed less communicative gestures than their peers in the comparison group. These differences between the two groups in their mode of communication led to the emergence of two distinct patterns of engagement which depict the different level of intentionality that these groups have in sharing their experiences during mother-child interactions. These representative patterns of interaction can be used as a potential tool for early identification of children at risk of ASD well before other behaviors become fully manifested.